The new proposed method for texture modification of closed up face image based on image processing using local weighting pattern (LWP) with enhancement technique - Fanany Onnilita Gaffar, Achmad; Shyafary, Darius; H, Rony; Baramanto Wicaksono Putra, Arief (International Journal of Engineering and Technology, 2018)
The texture is a two- and three-dimensional design element that is distinguished by the visual and physical properties perceived. Textured areas in the image can be marked with uniform or varying spatial intensity distribution. There are many techniques and methods from simple to sophisticated which available including machine learning-based methods to modify the texture map. The texture feature description becomes a new challenge in the field of computer vision and pattern recognition since the emergence of the local pattern binary method (LBP). This study proposes a new method called Local Weighting Pattern (LWP) for modifying textures based on the pixel's neighborhood of an RGB image. The results of this study obtained that LWP method produces a texture with a unique and artistic visualization. The Log function has been used to improve the image quality of the LWP method.Â Â